A new species and endemism of Tigridia (Tigridieae, Iridaceae) in the Transmexican Volcanic Belt, Mexico - López-Pérez, Jorge David; Rodríguez, Aarón; Munguía-Lino, Guadalupe (Phytotaxa, 2023)
The Transmexican Volcanic Belt (TVB) extends across Mexico from east to west between 18°30’ and 21°30’ latitudes. It is part of the Mexican Transition Zone consisting of several plateaus at different elevations and hundreds of volcanic structures. These have promoted diversification and endemism in several plant lineages. Here, Tigridia azufresensis is described as a new endemic species of the TVB. Morphologically, this taxon belongs to the Violacea complex and is similar to T. durangensis. Tigridia azufresensis differs from other species in its robust habit, and larger flowers. It has a cauline leaf subtending the rhipidium, so it appears to have three spathe valves. The flowers have elliptic to elliptic-lanceolate outer tepals and clawed inner tepals, which have a geniculate blade and a triangular apiculate limb. The TVB is rich in endemic species of Tigridieae: Tigridia azufresensis, T. flammea, T. gracielae, T. matudae, and T. venusta are exclusive to this biogeographical province.